THE IMPLEMENTATION OF VIRTUAL PBL (PROJECT BASED LEARNING) MODEL IN ENGLISH DRAMA COURSE - Sandra Dewi Dahlan (International Conference on Social and Islamic Studies, 2021)
This study aimed to describe the implementation of virtual Project Based Learning modelin English Drama course and to evaluate students’ response toward its implementation.This study used mixed methods to integrate the qualitative and quantitative data. Thesubjects of the study were fourth semester students of class AG 5/6 of English andLiterature Department, Faculty of Adab and Humanities, UIN Alauddin Makassar. Theobject of research is English Drama course by applying Project Based Learning model inthe form of virtual drama performance. The research technique was carried out by meansof observations, interviews and surveys to answer research questions. The results showedthat most of the students responded positively to the implementation of the virtual dramaproject and considered the process and implementation successful, especially inproviding a positive correlation between drama theory and practice as the learningmethod in the English Drama course. Despite that the project was carried out online, butstudents have honed their various soft-skills which also enriched their multiple-intelligence through this Virtual Drama project.